Mathematical modeling of cancer growth process: A review - Tabassum, Shabana; Norhayati, Rosli; Mazma Sayahidatul Ayuni, Mazalan (IOP Publishing, 2019)
Although cancer is a leading cause of death, a little is known about the mechanism of its growth and destruction. Mathematical models explaining these mechanisms are crucial to predict the behaviour of cancer cells proliferation. Perusal of the literature dealing with mathematical modelling of cancer initiation, proliferation and metastases is abundant. Mathematical models to simulate the growth rate of the cancer cells have been derived from both deterministic and stochastic considerations. Early model of tumor growth by diffusion was first introduced and then set the scene for many later mathematical models for solid tumors. In this article we review the deterministic and stochastic models that have been developing to discuss the tumor growth initiation and proliferation. The findings and interpretations are summarized, and the main research issues are highlighted